Leveraging AI for Sustainable Marketing and Financial Efficiency: An Integrated Framework for Green Competitive Advantage - Dr. Soma Hazra, Dr. Shubham Rajpal; Ms.Nitika Goyal, Dr Mukesh Jethwani (European Economic Letters (EEL), 2025)
Purpose: In an era of digital revolution and environmental urgency, artificial intelligence (AI) has emerged as a critical component of business performance and sustainability. By analysing the numerous ways AI can enhance marketing ROI, financial efficiency, and environmental sustainability, this paper offers an integrated framework to achieve Green Competitive Advantage. Design: The study uses a qualitative analytical approach in conjunction with a literature review, real-world case studies (like Netflix, Domino's, Unilever, and Patagonia), and financial modelling (DuPont and Economic Value Added) to assess the connection between AI adoption and sustainable business practices. Findings: Research indicates that by increasing customer retention and simplifying campaign strategies, AI-driven personalisation significantly boosts marketing return on investment. AI-using companies exhibit quantifiable gains in shareholder value, asset turnover, and net profit margins. By reducing energy consumption and carbon emissions, artificial intelligence (AI) in operations—such as route optimisation and predictive analytics—supports corporate sustainability goals. However, the survey also identifies barriers, particularly for SMEs, including high adoption costs, skewed data, inadequate infrastructure, and complex regulations. Originality: The research advances theory by acknowledging AI as a strategic resource for long-term value generation and by aligning with the Resource-Based View, Stakeholder Theory, and Triple Bottom Line Framework. By connecting AI-enabled technologies to green finance, it also raises the concept of "Smart Sustainable Finance." The paper offers useful strategic guidance for SMEs, corporations, lawmakers, and educators on how to overcome challenges and ethically integrate AI. The study concluded that responsible and transparent AI application in accordance with ESG goals and ethical governance is necessary to obtain a competitive advantage and foster sustainable growth in the AI-driven economy.